Prediction and Prevention of Early-Onset Preeclampsia: Impact of Aspirin After First-Trimester Screening. Issue 1 (January 2016) - Park, F.; Russo, K.; Williams, P.; Pelosi, M.; Puddephatt, R.; Walter, M.; Leung, C.; Saaid, R.; Rawashdeh, H.; Ogle, R.; Hyett, J.
Abstract : Obstet Gynecol Surv 2016;71(1):11–13 Preeclampsia (PE) continues to be a significant cause of maternal and fetal mortality and morbidity in both developed and developing societies. The aim of the study undertaken was to assess the value of intervention with low-dose aspirin after first-trimester prediction of early PE in an unselected population.